ROLE OF DIGITAL TECHNOLOGIES TO THE DEVELOPMENT OF INTERNATIONAL FINANCIAL RELATIONS (World Bulletin of Management and Law, 2024)
Given the ever-increasing challenges of competition in the age of globalization, innovation is critical to the viability and prosperity of the economy. In this regard, in developed countries, innovation is the main pillar of the country's economic development, and it is viewed as one of the most important issues of government policy. This article analyzes the ways of introducing digital technologies in the financial system and the issues related to the experience of developed countries in this regard.